Arabic language and tongue violence in Arab satellite channels - بوو علي, نصير صالح (ALBAHITH ALALAMI, 2017)
This study aimed at identifying the effect of violence on speech disorders concerning Arab Broadcasting . Language is a pot of thought and a mirror of human civilization and communication tool, but the Arabic language is suffering a lot of extraneous terms them, particularly through the media. This study attempts to answer the following question: Is the phenomenon of linguistic duality in the Media reflected negatively on the rules of the classical language? The study deals with the explanation and interpretation of the phenomenon that has become slang exist in our Media More. And the study suggests re- consideration of the value in the Media ,hence the problem will be resolved.